DGI-039 Guide to the Preparation and Administration of Injectable Cytotoxic Drugs. (12th March 2013) - Morgado, M; Pinto, A; Oliveira, R; Morgado, S
Abstract : Background: The preparation of injectable cytotoxics is a key activity of many hospital pharmaceutical services. Due to the increasing availability of cytotoxic medicines, either branded or generic, the time spent by hospital pharmacists in search of information about reconstitution and/or dilution, storage and stability of these drugs has increased. In order to effectively respond to this need for information, it would be useful to have a database that holds all that information for all cytotoxic medicines currently available in Portugal. Purpose: To prepare a guide to the preparation and administration of all parenterally administered cytotoxics available in Portugal, which provides information on the reconstitution and/or dilution, storage and stability, routes of administration, infusion rate, as well as other relevant observations. Materials and Methods: Review of the summary of product characteristics (SPC) of all injectable cytotoxic drugs currently available in Portugal; consultation with the pharmaceutical manufacturers and analysis of the responses received. Results: A total of 153 injectable cytotoxic medicines were investigated (88 branded and 65 generic), comprising a total of 40 active substances. Of this total, 145 have marketing authorization in Portugal and 8 are used under special-use authorization. Significant variability in the information available about the reconstitution, dilution, storage, administration and stability was observed, when considering the different formulations of the same active substance, which depend on the manufacturer. In all, 32 manufacturers were asked to add additional relevant information that was not present in the SPC. The guide is available in electronic format and in A5 print format (handbook), which has proved to be very practical, fast and effective to use. Conclusions: The published guide is a valuable tool for all Portuguese hospital pharmacists who prepare parenterally administered chemotherapy, answering to most information needs on reconstitution, dilution, storage, stability and administration of injectable cytotoxic drugs. No conflict of interest.